Visual analysis of temporal data associated with cryptocurrencies - Barrionuevo, Mercedes (2023)
Cryptocurrencies have emerged as a novel and dynamic asset class in the financial landscape, attracting significant attention from investors and researchers alike. As the popularity and diversity of cryptocurrencies continue to grow, there is an increasing need to analyze and understand the temporal dynamics and patterns within their data. Therefore, the treatment of such data involves the application of a wide range of tools for analysis and exploration, including different visualization techniques. In this paper, we present CryptoVisualizer, an integral visual analysis tool for temporal data associated with cryptocurrencies. Our proposal integrates different visualization methods and interactions to empower users in exploring and understanding temporal patterns, trends, and relationships in cryptocurrency markets.